Chlamydia psittaci infection and associated infertility in sheep. - Papp, J R (1993)
Nineteen ewes were injected subcutaneously with the agent of enzootic ovine abortion, Chlamydia psittaci serovar 1, at 50 days gestation. Placental and fetal tissues were examined at 15 days postinfection and thereafter at ten day intervals. Placental infection was detected at 15 days postinfection. Only postinoculation sera collected from postinfected ewes contained antibodies reactive to C. psittaci. Five (26%) chlamydial infected ewes experienced inapparent fetal loss before day 105 of gestation. This finding is significant since C. psittaci infection in sheep is commonly associated with abortion and not infertility.